FEASIBILITY OF BLACK RICE FARMING IN SUBAK SERASON, PITRA VILLAGE, PENEBEL DISTRICT, TABANAN - Engracia Ximenes Amaral; Ni Ketut Karyati; I Gusti Agung Nyoman Dananjaya2 (Fakultas Pertanian dan Bisnis Universitas Mahasaraswati Denpasar, 2025)
Subak Serason, located in Pitra Village, Penebel District, Tabanan Regency, holds strong potential to be developed as a center for black rice cultivation an agricultural commodity with both economic value and cultural significance. This study aims to evaluate the cost structure, revenue, and income from black rice farming, as well as to assess its economic feasibility. The research method employs a farm feasibility analysis approach. The results show that the average total cost incurred per 20 ares of land is IDR 5,838,000, while the average revenue reaches IDR 9,350,000. Consequently, the average net income obtained by farmers amounts to IDR 3,512,000. The R/C ratio of 1.60 indicates that this farming activity is profitable and economically feasible for continuation. This study recommends that farmers receive technical guidance through agricultural extension programs to improve both yield and the quality of black rice. Additionally, to enhance its economic value, harvested crops should be processed into rice before being marketed, enabling higher selling prices and significant value addition.